It wasn’t me!: On the Structured Entities’ liability in the Public Offers of Securities in Peru - Arrús Bellido, Oscar (2014)
This article seeks to analyze the liability regulation of different agents which participate in public offer securities in Peru and the economic reasons for regulation for allocation of that liability.